Triangular Prism

Written by Jerry Ratzlaff. Posted in Solid Geometry

 

triangular prism 2triangular prismEdge formula

\(a = \frac {A_l } {h} - b-c   \)

\(b = \frac {A_l } {h} - a-c   \)

\(c = \frac {A_l } {h} - a-b   \)

Where:

\(a\) = edge

\(b\) = edge

\(c\) = edge

\(h\) = height

\(A_l\) = lateral surface area

Height formula

\(h = \frac {A_l   } {a+b+c } \)

Where:

\(h\) = height

\(A_l\) = lateral surface area

\(a\) = edge

\(b\) = edge

\(c\) = edge

Base Area formula

\(A_b = \frac {1}{4} \sqrt { -b^4 + 2 \left( b c \right)^2 +2 \left( b a \right)^2 -c^4 +2 \left( c a \right)^2 -a^4 } \)

Where:

\(A_b\) = base area

\(a\) = edge

\(b\) = edge

\(c\) = edge

Lateral Surface Area formula

\(A_l = \left( a+b+c \right)   h \)

Where:

\(A_l\) = lateral surface area

\(a\) = edge

\(b\) = edge

\(c\) = edge

\(h\) = height

Volume formula

\(V = \frac {1}{4} h \sqrt { -b^4 + 2 \left( b c \right)^2 +2 \left( b a \right)^2 -c^4 +2 \left( c a \right)^2 -a^4 } \)

Where:

\(V\) = volume

\(a\) = edge

\(b\) = edge

\(c\) = edge

\(h\) = height